Elective midline laparotomy closure: the INLINE systematic review and meta-analysis - Diener, Markus K.; Voß, Sabine; Jensen, Katrin; Büchler, Markus W.; Seiler, Christoph (Annals of surgery, 2010)
Objective: To evaluate the optimal technique and material for abdominal fascia closure after midline laparotomy, first by means of a precisely defined study population and follow-up period and second by the surgically driven aspects. - Methods: Overview of existing systematic reviews and meta-analysis of randomized controlled trials. A systematic literature search (Medline, Embase, and The Cochrane Central Register of Controlled Trials) was performed to identify randomized controlled trials in elective and emergency populations comparing suture techniques (continuous vs. interrupted) and materials (rapidly vs. slowly vs. nonabsorbable). Random effects conventional and cumulative meta-analyses were calculated and presented as odds ratios and the corresponding 95% confidence intervals. - Results: Five systematic reviews and 14 trials including 7711 patients (6752 midline incisions) were analyzed. None of the systematic reviews differentiated elective versus emergency laparotomy. The analysis of available primary studies revealed significant lower hernia rates using a continuous (vs. interrupted) technique (OR: 0.59; P = 0.001) with slowly absorbable (vs. rapid-absorbable) suture material (OR: 0.65; P = 0.009) in the elective setting, which was in contrast to the conflicting results of existing systematic reviews. No statistical heterogeneity was detected in the elective setting (I2 = 0%). Seven studies incorporating elective and emergency procedures revealed inconclusive and heterogeneous results (I2 = 45%-85%). No studies have evaluated closure methods solely in the emergency setting so far. - Conclusion: No further trials should be conducted for evaluation of technique and available materials for elective midline abdominal fascial closure, according to the results of our cumulative meta-analysis. Future trials will have to define the optimal closure strategy in the emergency setting and relevance of new suture materials and other strategies such as the use of prophylactic mesh in targeted subpopulations.
Gesehen am 02.02.2023